Re-imagining the vulnerability and risk framing of parents with mental illness and their children - Becca Allchin; Becca Allchin; Sophie Isobel (Frontiers Media S.A., 2024)
To elicit compassion and communicate urgency to policy makers and governments, researchers and program developers have promoted a narrative of vulnerability and risk to frame the experience of families when parents have been diagnosed with mental illness. Developed within a western medicalised socio-cultural context, this frame has provided a focus on the need for prevention and early intervention in service responses while also unintentionally 'othering' these families and individualizing the 'problem'. This frame has had some unintended consequences of seeing these families through a deficit-saturated lens that misses strengths and separates family members' outcomes from each other. This paper raises questions about the continued fit of this frame and suggests a need to reimagine a new one.